2020
DOI: 10.1158/1078-0432.ccr-20-1923
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures of BRCAness and Tumor Inflammation Define Subgroups of Early-Stage Hormone Receptor–Positive Breast Cancer Patients

Abstract: Purpose: Patients with estrogen receptor– and/or progesterone receptor–positive, early breast cancer benefit from hormonal treatment, yet high global death burdens due to high prevalence and long-term recurrence risk call for biomarkers to guide additional treatment approaches. Experimental Design: From a prospective, observational study of postmenopausal early breast cancer patients treated with tamoxifen or aromatase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Given that accumulating data support that the immune system plays a crucial role in breast cancer, and gene expression signatures of tumor inflammation define subgroups of early ER‐positive breast cancer [ 77 ], immunotherapy deserves to be explored in subgroups of ER‐positive patients. There is evidence that PD‐1/PD‐L1 signaling antagonists may have meaningful clinical activity in some patients with ER‐positive breast cancers [ 78 ].…”
Section: Novel Therapies and Ongoing Clinical Trialsmentioning
confidence: 99%
“…Given that accumulating data support that the immune system plays a crucial role in breast cancer, and gene expression signatures of tumor inflammation define subgroups of early ER‐positive breast cancer [ 77 ], immunotherapy deserves to be explored in subgroups of ER‐positive patients. There is evidence that PD‐1/PD‐L1 signaling antagonists may have meaningful clinical activity in some patients with ER‐positive breast cancers [ 78 ].…”
Section: Novel Therapies and Ongoing Clinical Trialsmentioning
confidence: 99%
“…Breast cancer is a heterogenous disease, both biologically and clinically, with a high degree of inter-and intra-patient variability that is intrinsic to the tumor cells and in the cellular and molecular composition of the tumor microenvironment (TME) [3][4][5][6][7][8]. Clinically, the diversity manifests in patients with respect to response to therapy and prognosis [3,[9][10][11][12][13].…”
Section: Introduction 1biology and Prognostic Biomarkers In Breast Cancermentioning
confidence: 99%
“…Liang et al reported that elevated levels of CXCL9 mRNA were associated with favorable outcomes in HR-negative breast cancer and CXCL9 was correlated with immune cell infiltration and immune-related biomarkers [ 43 ]. TIS score was developed as a predictive biomarker of ICIs from a large cohort of pembrolizumab-treated patients across nine different tumor types and the predictive utility of TIS score has been verified in many other studies [ 15 , 44 , 45 , 46 ]. Schroth et al reported that two gene signatures including BRCAness and TIS score, were associated with clinical outcome or presence of tumor immunogenicity in HR-positive early breast cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 92%
“…TIS score was developed as a predictive biomarker of ICIs from a large cohort of pembrolizumab-treated patients across nine different tumor types and the predictive utility of TIS score has been verified in many other studies [ 15 , 44 , 45 , 46 ]. Schroth et al reported that two gene signatures including BRCAness and TIS score, were associated with clinical outcome or presence of tumor immunogenicity in HR-positive early breast cancer [ 46 ]. TIS scores were strongly associated with stromal TIL infiltrates, but TIS and TIL features showed only partial overlap [ 46 ].…”
Section: Discussionmentioning
confidence: 92%